Discourses on Research and Researchers: The Case of Portuguese Associated Laboratories - Branco Sousa, Sofia (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
This paper aims to map knowledge produced by associated laboratories in Portugal using the two-phase model of discourse analysis proposed by Sousa and Magalhães (2013). We analyse the mission of associated laboratories to understand what is (are) the privileged form(s) of knowing in science and the actors involved in that process. We identify discourse organisers (phase one of the model) and the way discourses become dominant/excluded (phase two of the model). The application of the two-phase model of discourse analysis enables us to conclude that research is being constructed as academic science in a post-academic world and researchers are presented as “in training” or as professors.